Lower Erythrocyte GST activity in Autism Spectrum Disorder (ASD) patients compared to normal controls - Donna Hermawati,; Then, Sue-Mian; Tri Indah Winarni,; Sultana MH Faradz,; Rahman Jamal, (UKM Medical Molecular biology Institute, UMBI, 2011)
Glutathione S-transferases (GST) are antioxidant enzymes that play an important role in the cellular detoxification and excretion of environmental pollutants including heavy metals. GST mu (GSTM1) and G theta (GSTT1) are known to be highly polymorphic and homozygous deletions of these genes result in the lack of enzyme activity and when combined with decreased levels of antioxidants, they have been associated with the Autism Spectrum Disorder (ASD). This preliminary study was performed to investigate the role of GSTM1 and GSTT1 polymorphisms as risk factors of ASD associated with GST activity and phenotype expression. Fifty one ASD patients and 45 controls were recruited for GSTM1 and GSTT1 genotyping while 6 ASD patients and 8 controls were assessed for GST activity. The results showed no significant differences in frequencies of GSTM1 null, GSTT1 null and combination both genotype between ASD patients and controls. However the mean erythrocyte GST activity in ASD is significantly decreased compared with controls (p = 0.043). The mean erythrocyte GST activity is lower in the severely autistic group compare to the mild to moderately autistic group, although it was not statistically significant. Further investigations are needed with a bigger sample size, analyzing multiple GST genes and GST activity determination to find out the gene susceptibility of ASD and factors that contribute to the phenotype expression of ASD.